Analisis Penerapan Hukum dalam Pembentukan Lembaga Kerjasama Bipartit: Tinjauan Terhadap Kekosongan Hukum Pra dan Pasca Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2022 Tentang Cipta Kerja - Edwardina Effendy, Edrick; Evan, Eugenius (LPPM Universitas Ekasakti Padang, 2024)
Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation has affected the formation of Bipartite Cooperation Institutions (LKS Bipartit) between workers/labor and employers/companies in Indonesia. The legal vacuum in the formation of government regulations mandated by Law Number 13 of 2003 concerning Manpower and its amendments, namely Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation, has resulted in the determination of administrative sanctions that lack enforcement power and produce inconsistent regional policies. An analysis of Provincial Regulations in Central Java and Regional Regulations in Tangerang City shows differences in the regulation of administrative sanctions, reflecting legal uncertainty. In the framework of the formation of legislation, both regulations should have equal authority in stipulating administrative sanction provisions. The formation of Government Regulations as mandated by legislation is necessary to fill the legal vacuum and serve as a basis for regional governments to enact regional regulations expected to provide legal certainty and make Bipartite Cooperation Institutions a more effective forum in industrial relations in Indonesia